2011
DOI: 10.1002/jwmg.269
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term response of Dicamptodon tenebrosus larvae to timber management in southwestern Oregon

Abstract: In the Pacific Northwest, previous studies have found a negative effect of timber management on the abundance of stream amphibians, but results have been variable and region specific. These studies have generally used survey methods that did not account for differences in capture probability and focused on stands that were harvested under older management practices. We examined the influences of contemporary forest practices on larval Dicamptodon tenebrosus as part of the Hinkle Creek paired watershed study. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Gradient, substrate type, amount woody debris, and other stream habitat characteristics, have been identified as important factors associated with salamander biomass and abundance (Dudaniec andRichardson 2012, Clipp andAnderson 2014). Leuthold et al (2012) explored the impact of near stream clear-cut timber harvest on salamanders in southern Oregon two years after forest harvest, and found no significant effect of the forest management on Pacific giant salamanders. Substrate explained the majority of variability in salamander biomass in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Gradient, substrate type, amount woody debris, and other stream habitat characteristics, have been identified as important factors associated with salamander biomass and abundance (Dudaniec andRichardson 2012, Clipp andAnderson 2014). Leuthold et al (2012) explored the impact of near stream clear-cut timber harvest on salamanders in southern Oregon two years after forest harvest, and found no significant effect of the forest management on Pacific giant salamanders. Substrate explained the majority of variability in salamander biomass in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that abundance of juvenile Coho Salmon should be positively associated with the proportion of substrate composed of cobble or boulder, but we found the reverse to be true. This reversal may be because predators such as Coastal Cutthroat Trout and coastal giant salamanders also rely on larger cobbles and boulders for cover during low flows in summer (Andersen 2008;Leuthold et al 2012). This explanation, however, is partly countered by the fact that we This article is protected by copyright.…”
Section: Discussionmentioning
confidence: 99%
“…Although temperatures generally stayed below the 15.0 C and 16.0 C thermal preferences for these species, it is not known whether these small changes in temperature might have induced behavioural responses (e.g., Bernardo and Spotila, 2006;Bancroft, Baker, Searle, Garcia, & Blaustein, 2008), including increased movement (Chelgren & Adams, 2017) or changes in survival rates of coastal giant salamanders. For example, Chelgren and Adams (2017) found that timber harvest decreased survival for coastal giant salamanders whereas Leuthold, Adams, and Hayes (2012) found no immediate effect of timber harvest. Further, we do not know whether the site-to-site variability in preharvest stream temperatures, which can be important for thermal adaptation (Hossack, Corn, & Fagre, 2006), could have influenced responses to harvestrelated temperature changes.…”
Section: Discussionmentioning
confidence: 99%